Review of social water cycle research in a changing environment. (September 2016) - Lu, Shibao; Zhang, Xiaoling; Bao, Haijun; Skitmore, Martin
Abstract: The Social Water Cycle (SWC) is a macroscopic and open system in which water derives from, and eventually returns to, the natural water circulation system. The two flows are integrated via coupling patterns such as infiltration, etc. In recent years, SWC has been deeply affected by global climate change and the excessive expansion of human activities. Therefore, it is essential to upgrade the cycle. This paper firstly presents the related knowledge hierarchy, the dualistic water cycle between nature and society, coupling patterns and driving mechanisms, evolving processes of water volume and quality, and SWC modeling. Based on these items, the relevant theoretical research is reviewed and a forecast made on the orientation of future studies. The research is of great theoretical and practical significance in advancing towards a water-saving and anti-fouling society, practicing water demand management, and promoting the development of modern hydroscience, technical innovation systems and basin water resource management in China and similar developing countries.